Text and context. The National Museum of Decorative Arts as a source for the research in the History of Education - Villalba Salvador, María (Historia y Memoria de la Educación, 2019)
This article considers the parallels and the relationships between the context of creation of the current National Museum of Decorative Arts (Spain), formerly National Museum of Industrial Arts, in the second half of the XIX century, together with the National Pedagogical Museum and the principles of the Institución Libre de Enseñanza (Free Teaching Institution). It highlights the connections and parallels with regard to the principles and actions of the two institutions at their beginnings and in their missions, as well as drawing comparisons with other cases in the Spanish and European contexts. Based on the evidence that there are numerous coincidences in many of the collections’ approaches, procedures and elements, we propose a line of work that takes into account the collections of institutions related to applied arts ―either museums or home museums―, and those of the educational museums, in order to more effectively teach Art History and the History of Education in Spain. Looking back into the past to the parallels between the two museums can provide a meaningful picture of part of the educational and social interests of the first third of the XX century